Comparative Study of Muslim Minorities: A Preliminary Framework (American Journal of Islam and Society, 1991)
Most of the world’s Muslims reside in countries where they are numericallypredominant. As such, these Muslims possess a majoritarian outlook in sharpcontrast to the perspective of minority Muslims living in India, China, theUSSR, and some Western countries. In recent years, Muslim minorities havefound themselves at the confluence of diverse social forces and politicaldevelopments which have heightened their sense of communal identity andapprehension vish-vis non-Muslim majorities. This has been particularlytrue of the crisis besetting the Indian Muslims in 1990-91 as well as the newlyformed Muslim communities in Western Europe.The foregoing circumstances have highlighted the need for serious researchon Muslim minorities within a comparative framework. What follows is apreliminary outline of a research framework for a comparative study of Muslimminorities using the Indian Muslims as an illustrative case.The Salience of TraditionOne of the most significant transnational phenomena in the four decadessince mid-century has been the revival of communal consciousness amongminorities in a large number of countries throughout the world. This tendencytoward cultural regeneration has been noted among such diverse ethnic groupsas Afro-Americans, French Canadians, Palestinian Arabs, the Scots of GreatBritain, Soviet minorities, and native Americans. A common tendency amongthese groups is to reach back to their cultural traditions and to explore thoseroots which have served as the historical anchors of their present communalexistence. Significantly, this quest for tradition has had a salutary impactupon the lives of these communities, for it has reinforced their collectiveand individual identities and has enabled them to confront the multipledifficulties of modem life more effectively. By according its members a sense ...